Perencanaan Strategis SI/TI pada PT Dilia Utama menggunakan pendekatan Ward & Peppard: - - Redho, Muhammad; Nova Wardani, Kiky Rizky (Universitas Lembah Dempo, 2022)
Abstract IS/IT strategic planning at PT Dilia Utama is a step to align IS/IT in accordance with the strategy and business processes of the Company. The purpose of this research is to produce an information technology strategy as the design of a future system portfolio. IS/IT strategic planning uses the ward & peppard approach by conducting internal and external analysis of the IS/IT business. The results of this study are in the form of a portfolio of applications proposed to support business activities, namely the Personnel Information System (hris), Partnership Information System (e-CRM), and SAP applications, as well as the addition of hardware, namely a server to accommodate data from the 3 systems that will be used. used later, as well as the addition of PCs and other hardware for business needs and also made to target system development, hardware additions and others in the next 5 years. Keywords: IS/IT strategic planning, Ward & Peppard, Application portfolio..